Kesalahan Penggunaan Kata-Baku Pada Salindia-Salindia Presentasi Mahasiswa Semester 3 UNINDRA - Maguna Eliastuti; Tri Astuti; Muhamad Andika Saputra; Fadiya Lathifa Putri Arfianto; Awalia Jumini; Alfiani Damayanti; Annisa Rizqiani; Eva Flora Wani Purba; Oktavianus Dore Paron; Risa Amelia Putri (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
This study-aims to obtain a-clear picture of information on errors in-the use of standard words in the presentation slides of Unindra's 3rd semester students. Suwito1 (1983: 3159) states that the standard language is one that must be used as a standard because it is seen as fulfilling the criteria of a number of good and correct languages. This shows that it is appropriate that the-use of standard-language in Indonesian society, especially for the scope of students is very important. Therefore, we made this research to-find out-how-high the-level-of standard words used by students is. The steps for analyzing the data are 1) Analyzing the data set, this analysis includes: noting which data are non-standard words and entering non-standard word data into the justification table. 2) After the analysis of the stages above, the researcher counted the occurrence of non-standard words, namely from the non-standard number. With this result, we can find out how many times the non-standard word is used.